First light : a history of creation myths from Gilgamesh to the God-particle - Evans, G. R. (Gillian Rosemary) (London : I.B. Tauris, 2014)
Did the universe start with a bang, or has it existed always? Was there a supernatural being behind it all, or just mindless forces? The beginning of things has forever tested the limits of curiosity, and such questions have both challenged atheists and inspired believers. Ancient cultures resorted to myth and symbolism to tell vibrant stories about human origins. Later civilizations added philosophical and scientific explanations: but these are not definitive. The nature and meaning of existence, the "why" as much as the "how" questions, are in the end mysterious. In this book the author explores the world's myriad creation stories against the background of the biggest question there is: what are we doing here? Discussing Swahili legends that resemble the Book of Genesis, Greek tales about the Titans, Native American, Inca and Mesopotamian mythologies, and Vedic creation cycles that begin with a cosmic egg or seed, the author surveys polytheist, monotheist and dualist ideas about supernatural power. Tracing the history of humanity as it has struggled, over many millennia, to make sense of itself, The Creation Myth will attract students of religion, history and philosophy and general readers alike. -- From publisher's website.
The universe begins. Disagreements about first principles. -- Why it is difficult to agree. What is the evidence? ; The great rival religious theories ; Choosing an approach ; Going to see. -- The main competing explanations. The beginning of the world: a one-off event? ; Creation as a system: initiation followed by a process of planned development? ; The search for a key.
Includes bibliographical references (pages 287-294) and index.
Keywords: Creation -- Mythology; Creation -- History of doctrines